171k views
17 votes
Given that a=4, b=3 and c=-4 work out b(squared) -2ac

Given that a=4, b=3 and c=-4 work out b(squared) -2ac-example-1

2 Answers

6 votes

Answer:

41

Explanation:

b^2 - 2ac plug in the values

3^2 -2(4)(-4) start with the exponent (remember PEMDAS)

9 -2(4)(-4) start multiplying from left to right

9 -8(-4) multiply

9 + 32 add

41 that's your answer :)

User Roman Kolpak
by
4.3k points
5 votes

Answer:

41

Explanation:

b^2 -2ac

Let a=4 b=3 c=-4

( 3)^2 -2 (4) (-4)

Exponents first

9 - 2 (4) (-4)

Multiply

9 + 32

41

User HaveAGuess
by
4.6k points